The productive structure of soybean and its impact: a comparative study between Paraguay, Argentina and Uruguay - González, Rafael Dário (Departamento de Economia, 2014)
The presented text aims to evaluate the causes that led to the formation of the current agrarian structure in Paraguay, Argentina and Uruguay as well as the characteristics of the agro-export model that takes place in these countries, which is based on production and export of soybeans. Because of its contemporary importance and represent the bulk of agricultural production in the countries under study, is established the objective of identifying the particularities and commonalities between these soybean production, with regard to its production structure and the benefits and impacts generated by this. Finally, statistical historical data are presented, enabling this comparison, showing the development and crucial moments for the establishment of the current standard.